TECHNOLOGICAL BASED INCUBATOR AND UNIVERSITY: A CASE STUDY IN THE REGION OF ITAJAÍ VALLEY - Miranda, Ronaldo Leão de; Domingues, Maria Jose Carvalho de Souza; Santos, Luís Fernando Irgang dos; Sestino, Andrea (Revista Ciências Sociais em Perspectiva, 2021)
By understanding organizations in depth, it is possible to perceive some interactions of organizations with other organizations and with their environment. This research aims to understand the dimensions that explain the relationship network existing between a technology-based incubator and a university located in the region of the Itajaí valley. Methodologically this study is characterized as descriptive in relation to its objective, as for the procedures it can be considered as applied research from the survey of primary data and qualitative in relation to the approach of the problem. Thus, the main results have identified that the main relationship between the incubator and the university lies in the structure of the board of directors of the incubator, where the dean of administration is the chairman of the incubator's board. Therefore, although there are some deficiencies in the relations between institutions, it can be considered as the bridge of success.